Strategi Pembelajaran TIK (Teknologi Informasi dan Komunikasi) - F, Fitriani; U., M. Shabir; U, Usman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of the era demands individuals to have 21st century skills, such as critical thinking, creativity, collaboration, and communication skills. ICT-based learning media can be an effective means to develop these skills. However, there are still many teachers who have not been trained in utilizing ICT for this purpose. With a qualitative descriptive approach, this study reveals ICT learning strategies. The results of the study indicate that ICT learning strategies have great potential to improve the quality of learning. By utilizing various available tools and applications, teachers can create a more interactive, interesting, and effective learning environment. However, it should be remembered that ICT is only a tool. The most important thing is how teachers can integrate ICT into learning effectively and in accordance with the learning context.